Full-field face vibration measurement in singing—Case study. (May 2021) - Frič, Marek; Hruška, Viktor; Dlask, Pavel
Highlights: Full-field measurement of facial vibrations employing electronic speckle pattern interferometry (ESPI). First formant tuning resonance effect. Standing waves dominate in the oscillations of the face. The biggest velocities and displacement measured in resonance effect when the first harmonics match the first formant. Abstract: This–> study presents a full-field measurement of facial vibrations employing electronic speckle pattern interferometry (ESPI) on one male subject. The measurement was performed in three states of mutual position of the first formant and fundamental frequency, where an effect of resonance of the vocal tract could be expected. Synchronous measurements of facial vibrations employing an accelerometer confirmed the dominance of the harmonic component closest to the position of the first formant in the entire area of the head and neck. In addition to the amplitude ratios of facial surface oscillations, ESPI also distinguished the phase differences. Standing waves dominate in the oscillations of the face. The area around the corners of the mouth always oscillated most strongly and coincided with the oscillation of the upper neck. Above the lower jaws, there was a hint of a travelling wave that progressed from the mandible angle towards the mouth corner and the neck. The biggest velocities and displacement measured in F4 for vowel /u/ could be explained as a resonance effect when the first harmonics match the first formant.